2001
DOI: 10.1046/j.1365-2036.2001.01118.x
|View full text |Cite
|
Sign up to set email alerts
|

Rabeprazole‐based 3‐day and 7‐day triple therapy vs. omeprazole‐based 7‐day triple therapy for the treatment of Helicobacter pylori infection

Abstract: INTRODUCTIONIn the Asia-Paci®c consensus conference on the management of Helicobacter pylori infection, the recommended regimens included the use of a proton pump inhibitor at a standard dose, plus two antibiotics (clarithromycin, amoxicillin or metronidazole), each given twice daily for 7 days. This regimen should attain a per protocol eradication rate of at least 90%, or an intention-to-treat eradication rate of at least 80%. 1 The high eradication rates of these combinations have been con®rmed in Western co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 26 publications
(36 reference statements)
2
31
0
Order By: Relevance
“…However, five RCTs (16,(21)(22)(23)(24) evaluating 934 patients were found that compared the equivalent doses of rabeprazole and omeprazole in PAC regimens. Meta-analysis of these trials suggests that rabeprazole is superior to omeprazole (RRR 8%, 95% CI 2% to 14%; NNT 16, 95% CI 9 to 65) ( Figure 3).…”
Section: Optimum Ppimentioning
confidence: 99%
See 1 more Smart Citation
“…However, five RCTs (16,(21)(22)(23)(24) evaluating 934 patients were found that compared the equivalent doses of rabeprazole and omeprazole in PAC regimens. Meta-analysis of these trials suggests that rabeprazole is superior to omeprazole (RRR 8%, 95% CI 2% to 14%; NNT 16, 95% CI 9 to 65) ( Figure 3).…”
Section: Optimum Ppimentioning
confidence: 99%
“…Indeed, American guidelines recommend 10 days of therapy, while European guidelines suggest that seven days is sufficient {1,48}. Shortening the duration of triple therapy to less than seven days has been shown to have a deleterious effect on eradication rates (23,48).…”
Section: Strategies To Improve Existing Regimens Optimum Duration Of mentioning
confidence: 99%
“…A significant reduction of adverse effects was observed with the use of a shorter (n=338) Excluded (n=248) because: 233 titles not appropriate; 9 articles in Spanish, German, and Japanese; 3 commences, letters; 3 studies on children Abstracts retrieved (n=90) Excluded (n=70) P<0.001), the day number with side-effects was reduced by an average of 3.5 d per patient in this study protocol in studies conducted by Wong et al (2001b). It was reported that the mean duration of all adverse effects was significantly shorter in the 3-d RAC (rabeprazole, amoxicillin, and clarithromycin) group when compared to the 7-d RAC group (2.8 d vs. 6.0 d, P<0.001) (Wong et al, 2001a).…”
Section: Adverse Events and Compliancementioning
confidence: 73%
“…They came from studies conducted in eight regions from six countries (Table 1). To make paired comparison convenient, one matched study arm was omitted from Wong et al (2001a) 's, Pieramico et al (1998) 's, and Yang et al (2003)'s trials, respectively.…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…The trial results showed that 7-d therapy with rabeprazole-clarithromycin-amoxicillin is similar in efficacy to 10-d therapies and had similar efficacy in patients with and without ulcer disease. Wong et al [29] performed a randomized study to compare rabeprazole-amoxicillinclarithromycin administration for 3 and 7 d. They found 3-d regimen had a lower H pylori eradication rate than 7-d regimen (72% vs 88%, ITT; 72% vs 91%, PP). Hence, they concluded 7-d rabeprazole-based triple therapy is superior to 3-d regimen (P = 0.04).…”
Section: Discussionmentioning
confidence: 99%